The Effect of Informative Values on Consumer Engagement in Digital Content Marketing: A Study of Consumers on TikTok on Indonesia - Kinanti, Annisa Wanda; Adi, Pramono Hari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of consumer engagement mediation on the causal relationship of informative value on consumer buying interest moderated by product type (search product vs experience product) on the TikTok platform. This research is a type of quantitative research using a survey method conducted by distributing questionnaires to TikTok users throughout Indonesia. The sample determination was carried out using the purposive sampling method, with 212 TikTok users divided into 104 sample search products or 108 sample experience products. The data obtained were analyzed descriptively and using the SmartPLS Structural Equation Model. The results of the research show that: (1) the informative value has a significant effect on consumer engagement, (2) the influence of informative value is higher on search products compared to experience products. In order to increase consumer engagement, sellers on TikTok can increase content that is of value to consumers as an effort to increase consumer engagement with digital content marketing, especially emphasizing the informative value of search products